Rolipram, a PDE4 Inhibitor, Enhances the Inotropic Effect of Rat Heart by Activating SERCA2a - Huang, Huili; Xie, Ming; Gao, Li; Zhang, Wenhui; Zhu, Xiaojia; Wang, Yuwei; Li, Wei; Wang, Rongrong; Chen, Kesu; Boutjdir, Mohamed; Chen, Long (Frontiers in Pharmacology, 2019)
This study was designed to investigate the hemodynamic effect of rolipram, a phosphodiesterase type 4 (PDE4) inhibitor, in normal rat hearts both in vivo and in vitro and its underlying mechanism. The pressure-volume loop, isolated heart and Ca2+ transients triggered by field stimulation or caffeine were used to analyze the hemodynamic mechanism of rolipram. The results demonstrated that rolipram (3 mg/kg, ip) significantly increased the in vivo rat heart contractility by enhancing stroke work, cardiac output, stroke volume, end-systolic volume, end-diastolic volume, end-systolic pressure, heart rate, ejection fraction, peak rate of rise of left pressure (+dp/dtmax), the slopes of end-systolic pressure-volume relationship (Slope of ESPVR) or named as left-ventricular end-systolic elastance and reduced the slopes of end-diastolic pressure-volume relationship (Slope of EDPVR). Meanwhile the systolic blood pressure, diastolic blood pressure and pulse pressure were significantly enhanced by rolipram. Also, rolipram deviated normal ventricular-arterial coupling without changing the arterial elastance. Furthermore, rolipram (0.1, 1, 10 µM) also exerted positive inotropic effect in isolated rat hearts by increasing the left ventricular development pressure, and +dp/dtmax in non-paced and paced modes. Rolipram (10µM) increased the SERCA2a activity, Ca2+ content andCa2+ leak rate without changing diastolic Ca2+ level. Rolipram had significant positive inotropic effect with less effect on peripheral vascular elastance and its underlying mechanism was mediated by increasing SERCA2a activity. PDE4 inhibition by rolipram resulted in a positive inotropic effect and might serve as a target for developing agents for the treatment of heart failure in clinical settings.